2018
DOI: 10.3982/ecta14434
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Inference in a Class of Regression Models

Abstract: We consider the problem of constructing confidence intervals (CIs) for a linear functional of a regression function, such as its value at a point, the regression discontinuity parameter, or a regression coefficient in a linear or partly linear regression. Our main assumption is that the regression function is known to lie in a convex function class, which covers most smoothness and/or shape assumptions used in econometrics. We derive finite‐sample optimal CIs and sharp efficiency bounds under normal errors wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
156
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 118 publications
(182 citation statements)
references
References 54 publications
2
156
0
Order By: Relevance
“…Remark Theorem does not address whether further efficiency improvements are possible by using estimators that do not fall into the class trueTˆfalse(h;kfalse), or by using variable length CIs. However, it follows from Donoho () and Armstrong and Kolesár () that, in typical settings where our results hold, little further improvement is possible. In particular, these papers give efficiency bounds that, applied to our setting, yield asymptotic lower bounds for Rfalse(trueTˆ*false)false/Rfalse(trueTˆfalse(h*;k*false)false), where trueTˆ* is the optimal estimator or CI among all procedures (for CIs, this includes variable length CIs, with performance measured in terms of expected length), and h* and k* are the optimal bandwidth and kernel.…”
Section: General Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…Remark Theorem does not address whether further efficiency improvements are possible by using estimators that do not fall into the class trueTˆfalse(h;kfalse), or by using variable length CIs. However, it follows from Donoho () and Armstrong and Kolesár () that, in typical settings where our results hold, little further improvement is possible. In particular, these papers give efficiency bounds that, applied to our setting, yield asymptotic lower bounds for Rfalse(trueTˆ*false)false/Rfalse(trueTˆfalse(h*;k*false)false), where trueTˆ* is the optimal estimator or CI among all procedures (for CIs, this includes variable length CIs, with performance measured in terms of expected length), and h* and k* are the optimal bandwidth and kernel.…”
Section: General Resultsmentioning
confidence: 76%
“…Our asymptotic approach allows for simplifications that deliver our main relative efficiency results. These efficiency results are different from and complementary to the asymptotic form of the efficiency bounds given in Donoho () and Armstrong and Kolesár (): whereas we consider relative efficiency of estimators and fixed‐length CIs based on different kernels and bandwidths, Donoho () and Armstrong and Kolesár () bound the scope for efficiency gains from CIs that do not fall into this class. Donoho () and Armstrong and Kolesár () found that the scope for further improvement is small, which motivates our focus on this class of estimators and CIs.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations